HUBUNGAN ANTARA BEBAN KERJA MENTAL DENGAN STRES KERJA DOSEN DI SUATU FAKULTAS - Pertiwi, Ella Marliani; Denny, Hanifa Maher; Widjasena, Baju (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Universities are the main pillar in the education system that is as a supporter of qualified human resources (HR). Therefore, lecturers are important components that determine whether a higher education is developed in academics or not. The number of demands and responsibilities that the lecturers should take, plus the environmental conditions and other triggering factors if the lecturers cannot adapt themselves then this will give pressure to the lecturers which will cause stress. The purpose of this research is to know the existence of the relation between mental workload and work stress of lecturers at Faculty, X University. This research used Cross Sectional design. The population is the lecturers in Faculty X, X University in Semarang. The sample taking was done by total sampling technique, the sample in the research was 50 respondents. The independent variable is mental workload and the dependent variable is work stress. Data were collected by using a General Health Questationary (GHQ) -12 questionnaire to measure the work stress, while to measure the mental workload, it used questionnaires referring to NASA-TLX. The data obtained were analyzed by using Product Moment Pearson statistic test with the significance level of p = 0,05. The results showed that there is a relation between workload and work stress (ρ value: 0.25). The researcher suggested the Faculty to do mapping for lecturers’ workload in order to make it more structured.